Pengaruh Profitabilitas dan Likuiditas Terhadap Nett Working Capital (Studi Kasus PT Telkom Indonesia Tahun 2017-2021) - Muhammad Distian Andi Hermawan (Strategic: Journal of Management Sciences, 2023)
PT Telkom Indonesia must be able to increase profits or maximum profits in order to maintain the stability of its financial performance and also on the one hand the company must be able to maintain its liquidity level in order to support and get maximum profits compared to previous year. The method used in this study is using secondary data and analysis tools, namely SPSS Version 24. The test results above show that the variable Profitability value of the sig is 0.276>0.05 so it can be said that the variable profitability has no influence on the Deependent variable, the Sig Value of the Liquidity Variable is 0.029> 0.05. The test results above show that the variable Profitability sig value is 0.276>0.05 then it can be said that the profitability variable has no influence on the Deependent variable, the Sig Value of the Liquidity Variable is 0.029> 0.05 then it can be said that the independent variable X2 does not have a significant influence on the Dependent Variable (X). The results of the study simultaneously showed a Sig value of 0.034>0.005 which is greater than 0.005 so it can be said that together (simultaneously) the independent variables Profitability and Liquidity have no influence on the Dependent Variable (NWC).